Estimation of the optimum dose of vitamin D for disease prevention in older people: Rationale, design and baseline characteristics of the BEST-D trial. Issue 4 (April 2015) - Clarke, Robert; Newman, Connie; Tomson, Joseph; Hin, Harold; Kurien, Rijo; Cox, Jolyon; Lay, Michael; Sayer, Jenny; Hill, Michael; Emberson, Jonathan; Armitage, Jane
Highlights The BEST-D (Biochemical Efficacy and Safety Trial of vitamin D) trial will compare the biochemical and other effects of daily dietary supplementation with 100 μg or 50 μg vitamin D3 or placebo, when administered for 12 months, in 305 ambulant community-dwelling older people living in Oxfordshire, England. The primary analyses will compare 12-month mean plasma concentrations of 25(OH)D as well as the proportion of participants with a 12-month concentration >90 nmol/L between participants allocated 100 μg and participants allocated 50 μg daily. Secondary analyses will compare the two active doses (both separately and when combined) with placebo. Additional end-points include biochemical assessments of safety, blood pressure, arterial stiffness, falls, fractures, heel and wrist bone density, grip strength and physical performance and echocardiographic assessments of cardiac function in a random sample of participants. The results of this trial will help determine the optimum dose of vitamin D to test in a larger trial investigating whether vitamin D supplementation can reduce the risk of fractures, cardiovascular disease or cancer.